Pilot contamination reduction in very large MIMO cellular network - Hai-rong WANG; Yu-hui WANG; Yong-ming HUANG; Lv-xi YANG (Tongxin xuebao)
Two pilot contamination reduction methods in very large MIMO cellular network were proposed by dividing all cells into two types of one-dimensional very large MIMO network.The same pilot sequences were used in cells in the same category while orthogonal pilot sequences were used between these two categorie.Then the pilot power control method can be used to achieve the purpose of alleviating pilot contamination.By coordinating among base stations,the nearly optimal length of pilot sequences and assignment of pilot transmission could be found through minimizing the sum of channel estimation mean square error of all base stations.Thus,much better performance of channel estimation could be obtained,greatly enhancing the sum rate in downlink in all cells.